1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mutations in Hexose‐Transporter Genes on Glucose Repression in Kluyveromyces Lactis

Abstract: The variability of Kluyveromyces lactis strains in sensitivity to glucose is correlated with genetic differences in Kluyveromyces hexose transporter (KHT) genes. The glucose sensitive strain JA6 was shown to contain an additional gene, KHT2, not found in strains that are less sensitive. KHT2 is tandemly arranged with KHTI which is identical to the low-affinity transporter gene RAGI, except for the Cterminus. Sequence analysis indicated that most of KHT2 had been lost by a recombination event between KHTl and K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 55 publications
(67 reference statements)
1
62
0
Order By: Relevance
“…This implies that the balance between respiration and fermentation in this yeast depends on oxygen availability and not on glucose concentration (Weirich et al, 1997;Kiers et al, 1998;González-Siso et al, 2000). The key point of the balance between respiration and fermentation is the branch point of pyruvate metabolism, with pyruvate being either oxidized by the respiratory enzyme pyruvate dehydrogenase (PDH) or decarboxylated by the fermentative enzyme pyruvate decarboxylase (PDC).…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the balance between respiration and fermentation in this yeast depends on oxygen availability and not on glucose concentration (Weirich et al, 1997;Kiers et al, 1998;González-Siso et al, 2000). The key point of the balance between respiration and fermentation is the branch point of pyruvate metabolism, with pyruvate being either oxidized by the respiratory enzyme pyruvate dehydrogenase (PDH) or decarboxylated by the fermentative enzyme pyruvate decarboxylase (PDC).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of glucose signaling in glucose-repressible strains of the Crabtree-negative yeast Kluyveromyces lactis, used increasingly as a model organism in comparative functional genomics (10 -12), is largely unknown; however, the unique hexokinase KlHxk1 encoded by the RAG5 gene, the expression of glucose transporters, and the capacity for glucose transport seem to be involved (13)(14)(15).…”
mentioning
confidence: 99%
“…We propose that the upregulation of HXT7 observed in the HXT7-only strain, compared to the wild-type, is also due to relief of glucose repression resulting from reduced transport capacity and intracellular concentrations of glucose, and cannot be accounted for by alterations in glucose signalling that are independent of glucose metabolism (Liang and Gaber, 1996). A number of laboratories have found that wild-type levels of glucose transport capacity are required for normal glucose repression of various genes, including those involved in respiration, gluconeogenesis and utilization of alternative carbon sources such as sucrose and maltose (Gamo et al, 1994;Ö zcan et al, 1993;Reifenberger et al, 1997;Weirich et al, 1997;Ye et al, 1999). For example, the degree of glucose repression of maltase activity during growth on glucose plus maltose is correlated with the extent to which glucose transport capacity is reduced in HXT-only strains and the hxt1-hxt7 null strain.…”
Section: Glucose Repression and Glucose Transport Capacitymentioning
confidence: 99%